Seepage Characteristics of Slurry with Particle Additives in the High-Permeability Sand Layer - Yuan Wang; Zhikui Wang; Di Feng; Sijin Liu; Shujun Xu; Kun Zhou (Geofluids)
In the process of the slurry shield construction, the formation of the filter cake is the key to maintain the stability of the excavation face. In high-permeability formation, ordinary pure bentonite slurry is easy to pass through the formation void. Therefore, it is necessary to study the slurry permeability characteristics of the high-permeability sand layer. For the purpose of researching the permeability characteristics of slurry in sandy formation, this paper studies the influence of slurry viscosity on the formation of the filter cake in high-permeability formation under different pressure gradients by the slurry permeability test. The effect of additive particle size on the film-forming gain was studied by adding additives with different particle sizes into pure bentonite slurries with different viscosities. This paper presents a method to determine the optimum slurry viscosity and particle size for high-permeability formation so as to guide the slurry shield construction in high-permeability formation.